Making midwifery work visible: The multiple purposes of documentation. Issue 3 (June 2018) - Kerkin, Bridget; Lennox, Susan; Patterson, Jean
Abstract: Background: Midwives have a professional, ethical and legal obligation to effectively and thoroughly document the care provided to women and the decisions made within the partnership relationship. To appreciate the best approach to documenting midwifery care, it is important to first understand the purpose of midwifery documentation. Aim: The aim of this article is to explore the literature in relation to the purposes of midwifery documentation. Method: A literature search was performed using the CINAHL and Pubmed databases. Hand searching of reference and citation lists was employed to deepen the literature pool. Findings and discussion: No research articles with a midwifery focus were found addressing the purpose of documentation. Broader searching of literature from other healthcare fields was drawn on to identify the contribution of record keeping to: partnership and continuity of care; communication between health professionals; improved standards of care; audits and clinical reviews; research and education; the visibility of midwifery work; the reflective practices of midwives; professional accountability; the legal record of care; the narrative record of experience for women. Conclusion: The purpose of midwifery documentation is complex and multi-factorial, involving much more than the recording of clinical and legal details of a woman's care. Midwifery documentation may potentially enhance the maternity care experience for women, support the role of the midwife, positively impact collaboration between health professionals, and contribute to organisational processes and research. Further research is needed to clarify how to address the documentation priorities of women and midwives, within the context of the maternity record.